Аутоантитела к нейромедиаторам при алкоголизме и сочетании алкогольной зависимости с депрессией у мужчин - Vetrile, L. A.; Davydova, T. V.; Nevidimova, T. I.; Zakharova, I. A.; Savochkina, D. N.; Galkin, S. A. (Патогенез, 2022)
Тезисы конференции